1987
DOI: 10.1002/1097-0142(19870101)59:1<31::aid-cncr2820590111>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of methotrexate metabolism in rats by administration of an elemental liquid diet I. Changes in drug enterohepatic circulation

Abstract: Severe enteritis and death consistently occur within 150 hours of a single intraperitoneal dose of 25 mg/kg methotrexate given to rats fed an elemental diet. Rats fed a regular chow diet show no clinical evidence of gastrointestinal morbidity or mortality at this dose. The etiology of this enhanced toxicity is not clear, however. It this study rats were randomized to receive an elemental diet (n = 45) or a regular chow diet (n = 45) for 7 days. They were then given a bolus dose of 3H methotrexate (25 mg/kg) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A variety of feeds have been used in studies in adults 3738 Semihydrolysed diets have been shown to protect against the sequelae of abdominal radiotherapy in adults,39 while conversely, standard chow had advantages over elemental diet in rats receiving methotrexate 4024.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of feeds have been used in studies in adults 3738 Semihydrolysed diets have been shown to protect against the sequelae of abdominal radiotherapy in adults,39 while conversely, standard chow had advantages over elemental diet in rats receiving methotrexate 4024.…”
Section: Discussionmentioning
confidence: 99%
“…We have also used rectal dialysis for quantification of the post‐dose peak methotrexate concentration. Based on animal studies indicating that parenterally administered methotrexate concentration peaks in the intestine after 1–2 h, 13 , 14 we elected to schedule the dialysis procedure to span the drug’s anticipated intestinal t max . A time lag exists before equilibration across the dialysis membrane is complete, and analyte will diffuse out of the bag if the rectal concentration falls before the bag is removed.…”
Section: Discussionmentioning
confidence: 99%
“…Standard curves were prepared for correction for quenching as described previously. 2 In a second in vitro study, the binding of methotrexate by cholestyramine using bile as a buffer was examined. Three male Fischer rats underwent laparotomy and bile duct cannulation, as described previously.…”
Section: In Vitro Binding Of Methotrexate To Cholestyraminementioning
confidence: 99%
“…Three male Fischer rats underwent laparotomy and bile duct cannulation, as described previously. 2 The cannula was tunnelled to the back and, through a swivel sutured to the skin, brought out of the cage to a collection vial. Bile was collected continuously over 3 days and pooled for use as a buffer solution, replacing the phosphate buffer solution in the previous experiment.…”
Section: In Vitro Binding Of Methotrexate To Cholestyraminementioning
confidence: 99%